Detection of Coccolithophore Blooms With BioGeoChemical‐Argo Floats. Issue 23 (25th November 2020) - Terrats, L.; Claustre, H.; Cornec, M.; Mangin, A.; Neukermans, G.
Abstract: Coccolithophores (calcifying phytoplankton) form extensive blooms in temperate and subpolar oceans as evidenced from ocean‐color satellites. This study examines the potential to detect coccolithophore blooms with BioGeoChemical‐Argo (BGC‐Argo) floats, autonomous ocean profilers equipped with bio‐optical and physicochemical sensors. We first matched float data to ocean‐color satellite data of calcite concentration to select floats that sampled coccolithophore blooms. We identified two floats in the Southern Ocean, which measured the particulate beam attenuation coefficient ( c p ) in addition to two core BGC‐Argo variables, Chlorophyll‐ a concentration ([Chl‐ a ]) and the particle backscattering coefficient ( b bp ). We show that coccolithophore blooms can be identified from floats by distinctively high values of (1) the b bp / c p ratio, a proxy for the refractive index of suspended particles, and (2) the b bp /[Chl‐ a ] ratio, measurable by any BGC‐Argo float. The latter thus paves the way to global investigations of environmental control of coccolithophore blooms and their role in carbon export. Plain Language Summary: Coccolithophores are a group of phytoplankton that form an armor of calcite plates. Coccolithophores may form intense blooms which can be identified from space by so‐called ocean‐color satellites, providing global images of the color of the surface ocean. BioGeoChemical‐Argo (BGC‐Argo) floats, robots profiling down to 2, 000 m with a variety of physicochemical and bio‐optical sensors, present an increasingly attractive and cost‐effective platform to study phytoplankton blooms and their impact on oceanic biogeochemical cycles. We show that coccolithophore blooms can be detected by BGC‐Argo floats with high confidence, hence providing a new way to study them at the global scale as well as their role in sinking carbon. Key Points: We matched profiling float trajectories with ocean‐color satellite observations of coccolithophore blooms Two simple bio‐optical indices permitted successful identification of coccolithophore blooms from floats in the Southern Ocean A method for identifying coccolithophore blooms at the global scale is proposed using regional thresholds of bio‐optical float measurements